Biosurfactants and Their Applications in the Oil and Gas Industry: Current State of Knowledge and Future Perspectives - Nikolova, Christina; Gutierrez, Tony (Frontiers in Bioengineering and Biotechnology, 2021)
Surfactants are a group of amphiphilic chemical compounds (i.e. having both hydrophobic and hydrophilic domains) that form an indispensable component in almost every sector of modern industry. Their significance is evidenced from the enormous volumes that are used and wide diversity of applications they are used in, ranging from food and beverage, agriculture, public health, healthcare/medicine, textiles and bioremediation. A major drive in recent decades has been toward the discovery of surfactants from biological/natural sources – namely bio-surfactants – as most surfactants that are used today for industrial applications are synthetically-manufactured via organo-chemical synthesis using petrochemicals as precursors. This is problematic, not only because they are derived from non-renewable resources, but also because of their environmental incompatibility and potential toxicological effects to humans and other organisms. This is timely as one of today’s key challenges is to reduce our reliance on fossil fuels (oil, coal, gas) and to move toward using renewable and sustainable sources. Considering the enormous genetic diversity that microorganisms possess, they offer considerable promise in producing novel types of biosurfactants for replacing those that are produced from organo-chemical synthesis, and the marine environment offers enormous potential in this respect. In this review, we begin with an overview of the different types of microbial-produced biosurfactants and their applications, and then dedicate the remainder of this review to discussing the current state of knowledge and trends in the usage of biosurfactants by the Oil & Gas industry for enhancing oil recovery from exhausted oil fields and as dispersants for combatting oil spills.